CERITA PANJI DALAM PERSPEKTIF SEJARAH - Sunu Catur Budiyono (Jurnal Budaya Nusantara, 2018)
As a story which spread is dominated by oral tradition, Panji is presented in various versions. Meanwhile,history uses facts, data, or documents to be systematically explored and elaborated. In this case, history speaks in thedomain of "the logic of acceptability" whereas literature extends into the realm of "the logic of ignorance". If literatureand history serve the phrase "historical literature" and "literary history" then two things are different. Historicalliterature is part of a literary history study, but not the other way around. History literature stems from the belief ofsomething. Instead, history begins with the proof of something (Ibrahim, 1986: vii). The story of Panji is also the onlylocal story that is globalized. Panji is also appointed as a cultural hero of the archipelago. Starting from the abovediscussion, it is stated that historical literature can only be used to give an overview of civilization society, the concept of state administration, and the style of thinking in that era.